Developing material for English for Holiday program - Soviyah Soviyah; Nur Fatimah (English Language Teaching Educational Journal, 2021)
An English program like English For Holiday (EFH), is concerned with helping children to learn English. In relation to English Education Department of Universitas Ahmad Dahlan, the department has employed an EFH program to help children with English learning during their school break. To accomplish the continuous improvement of the program, it needs research related to it, as these kinds of research provides meaningful data and product, which are important for the improvement of the program’s quality. Generally, the ultimate aim of the research is to contribute to the establishment of a better EFH program, especially of English Education Department, Universitas Ahmad Dahlan. Specifically, this research aims to develop syllabus and material for EFH program of EED UAD. This research started in May and was complete in November 2020 at English Education Department of Universitas Ahmad Dahlan (UAD). It utilized Research and Development (R&D) type with ADDIE model initiated by McGriff (2000) which endeavors a development process encompassing five major stages i.e. analyze, design, develop, implement, and evaluation. The research results show that the EFH material is developed to fulfil the children’s needs of material for EFH program. The developed product offers an alternative solution to fill the children’s needs. Based on the evaluation, it is found out that the developed material is considered very good. Through this material, children participating in EFH program can learn English in an enjoyable way. Although the major target is to improve children’s speaking skill, through this material, children can learn and develop their other skills i.e. listening reading and writing as the developed material is written in an integrated way involving all four skills of English.